Deep serological profiling of the Trypanosoma cruzi TSSA antigen reveals different epitopes and modes of recognition by Chagas disease patients. - Guadalupe Romer; Leonel A Bracco; Alejandro D Ricci; Virginia Balouz; Luisa Berná; Juan C Villar; Janine M Ramsey; Melissa S Nolan; Faustino Torrico; Norival Kesper; Jaime Altcheh; Carlos Robello; et al. (Public Library of Science (PLoS), 2023)
Background Trypanosoma cruzi, the agent of Chagas disease, displays a highly structured population, with multiple strains that can be grouped into 6-7 evolutionary lineages showing variable eco-epidemiological traits and likely also distinct disease-associated features. Previous works have shown that antibody responses to 'isoforms' of the polymorphic parasite antigen TSSA enable robust and sensitive identification of the infecting strain with near lineage-level resolution. To optimize the serotyping performance of this molecule, we herein used a combination of immunosignaturing approaches based on peptide microarrays and serum samples from Chagas disease patients to establish a deep linear B-cell epitope profiling of TSSA. Methods/principle findings Our assays revealed variations in the seroprevalence of TSSA isoforms among Chagas disease populations from different settings, hence strongly supporting the differential distribution of parasite lineages in domestic cycles across the Americas. Alanine scanning mutagenesis and the use of peptides of different lengths allowed us to identify key residues involved in antibody pairing and the presence of three discrete B-cell linear epitopes in TSSAII, the isoform with highest seroprevalence in human infections. Comprehensive screening of parasite genomic repositories led to the discovery of 9 novel T. cruzi TSSA variants and one TSSA sequence from the phylogenetically related bat parasite T. cruzi marinkellei. Further residue permutation analyses enabled the identification of diagnostically relevant or non-relevant substitutions among TSSA natural polymorphisms. Interestingly, T. cruzi marinkellei TSSA displayed specific serorecognition by one chronic Chagas disease patient from Colombia, which warrant further investigations on the diagnostic impact of such atypical TSSA. Conclusions/significance Overall, our findings shed new light into TSSA evolution, epitope landscape and modes of recognition by Chagas disease patients; and have practical implications for the design and/or evaluation of T. cruzi serotyping strategies.